Analysis of Marketing Facilities available for Tomato Growers of Haryana - Kumari, Neelam; Chahal, Pardeep Kumar; Malik, Joginder Singh (Indian Journal of Extension Education, 2022)
Market plays crucial role in the economic life of farmers, and essential in the chain of commodity distribution. Postharvest losses in tomato are a matter of concern for all tomatoÂ growers, therefore a need for farmers to sell their produce instantly after harvesting is felt. Provision of better marketing facilities would assist in better handling of the produce andÂ reduce storage losses, thereby offering higher and remunerative prices to the growers. The present study was conducted during 2020-21 in four districts of Haryana, namely Nuh, Sonipat, Gurugram and Palwal. The investigation was focused on the marketing facilities available for the farmers, their knowledge and adoption level regarding post-harvest management practices. A total sample of 160 respondents were selected and personally interviewed. The results indicated that farmers had medium degree of mass media exposure, extension contact and extension participation. To test the adequacy of sample, factor analysis using KMO and Bartlettâ€™s test of sphericity was applied and yielded 10 factors and explaining a total of 69.58 per cent of the variance for the entire set of marketing facilities.